Possibility of controling sheep's and coat's milk pasteurization by alkalive phosphatase test - ΠΑΥΛΟΥ, ΡΟΖΑΚΗ; ΑΝΥΦΑΝΤΑΚΗΣ, ΕΜΜΑΝΟΥΗΛ (Journal of the Hellenic Veterinary Medical Society, 2019)
The alkaline phosphatase activity of cow's, sheep's and goat's milk was studied. For this, 62 milk samples taken during the lactation period were examined. It was found that phosphatase activity of cow's milk ranged from 1872 to 4740 μg phenol/ml average 3536, that of sheep's milk from 8301 to 17280 average 12445 and that of goat's milk from 228 to 636 average 455. The effect of different temperatures on the phosphatase activity of the three kinds of milk was also examined. The cow's milk phosphatase was found more resistant than the others. Sheep's and goat's milk phosphatase showed similar sensitivity but they gave different results when examined by the routine alkaline phosphatase test. It was found that this test can be used for the control of the pasteurization of sheep's milk as well as in cow's milk but not for the goat's milk.